Logistics Engineering And Supply Chain Management Development In Cooperation With China: Modern Trends And Practical Implementation (Eurasian Scientific Herald, 2026)
This study examines the development of logistics engineering and supply chain management in the context of international cooperation between Uzbekistan and China. The research analyzes modern trends in logistics systems, including digital transformation, smart logistics technologies, and efficient supply chain optimization. Special attention is given to China’s advanced experience in infrastructure development, transportation networks, and logistics innovation. The study highlights how cooperation between the two countries contributes to improving logistics efficiency, reducing transportation costs, and enhancing trade connectivity. The results show that the integration of Chinese logistics models into Uzbekistan’s system can significantly improve operational performance and economic competitiveness.